High prevalence and incidence of human immunodeficiency virus 1 among men who have sex with men at the voluntary counselling and testing center in Northeast Brazil (Research, Society and Development, 2021)
The human immunodeficiency virus (HIV) Brazil epidemic had shown an increase in heterosexual transmission and decrease in vertical transmission. However, its incidence has increased among men who have sex with men. Serological screening of patients at a voluntary counselling and testing center in Cabo de Santo Agostinho city, Pernambuco province, Northeast Brazil, was performed to determine the HIV-1 prevalence and incidence. The HIV-1 incidence in the frozen serum aliquots obtained from 2006-2009 was determined using BED-capture enzyme immunoassay. This study evaluated 23,862 individuals, who were serologically tested for HIV-1. HIV-1 infection was diagnosed in 318 individuals (1.33%). MSM showed a higher prevalence of infection (6.8%; 95% confidence interval [CI]: 4.9-9.5) as compared to heterosexual men (2.8%; 95% CI: 2.35-3.36) and women (0.9%; 95% CI: 0.76-1.0) (p < 0.0001). MSM also showed a higher rate of incidence with 3.93 per 100 people/year. Early diagnosis and preventive measures can reduce the pandemic spread.